Securing Healthy Circular Material Flows In The Built Environment: The Case Of Indoor Partitioning - Geldermans, Bob (A+BE | Architecture and the Built Environment, 2020)
Departing from two problem statements, one concerning circularity in the built environment and one concerning flexibility in the built environment, this dissertation sets out to answer two main research questions: – In an Open Building division of support and infill, to what extent can the infill contribute to sustainable circular material & product flows? – Which qualitative and quantitative criteria and preconditions are central to integrating the notions of user health & well-being, circularity, and flexibility in infill configurations? In view on these research questions, this dissertation revolves around multiple topics and disciplines, addressing material properties, material flows, product design, and user benefits, relating to a specific building component: non-bearing partitioning. The research follows a mixed-method approach, primarily qualitatively driven and supported by quantitative data and tools. Literature studies, workshops and expert consultations are applied throughout the trajectory to derive, test and adjust criteria, guidelines and design concepts. The dissertation is structured around four research chapters (each set-up as a separate academic article), preceded by a general introduction and background sketch, and followed by an overarching evaluation of the findings. The results from the first research chapter (Chapter 3) concern the distinction of various intrinsic and relational properties, as well as an inventory matrix based on building layers and material reutilisation routes. In the next chapter (Chapter 4), a first set of criteria is derived (Circ-Flex I) in order to integrate flexibility, circularity and user benefits. In Chapter 5, criteria are further elaborated, including assessment guidelines that pinpoint health, well-being, and operational performance (Circ- Flex II). The following chapter (Chapter 6) is aimed at design aspects: a design conceptualisation trajectory is laid out, applying design preconditions rooted in the criteria that were shaped in the preceding chapters. Furthermore, a novel flow analysis and modelling method is utilised with respect to secondary raw materials: the Activity-based Spatial Material Flow Analysis (AS-MFA). This stage revolves around materialisation and operational propositions for an innovative partitioning configuration of side-panel and insulation. The innovations are based on renewable material and reversible adhesive technologies. The following conclusions are derived from the research: Circularity in the built environment can only occur if flexibility is fully integrated in the whole building (component) value network, and conversely, flexibility in the built environment increasingly depends on the handling and management of materials designated for healthy, circular applications. Infill parts, implemented in an Open Building context, enable multiple short to medium length cycles within the longer service lives of multi-family building structures, following changes in user requirements. As such, this model accommodates more sustainable product and material flows. However, decisive success factors are the attitude of and interplay between actors in the value network, not least the end-user. Technical circularity potential of building products and materials resides at the intersection of intrinsic and relational characteristics. The differentiation of building layers and parts, in combination with differentiated reutilisation routes, provides leverage for more advanced approaches to circular building strategies, anticipating multiple handling and treatment processes. To bring circular building to scale in a socially engaged way, value models need to take account of actors’ shared incentives around flexibility and health, as well as split incentives around circularity. Monitoring the operational performance is key for capitalising on the intrinsic health and circularity potential of building components during their service life. Research and design exercises into circular building concepts and products benefit reciprocally from data and experience in adjacent disciplines, such as urban planning and waste management, whilst integrating multiple sub-systems associated with value creation in circular models. Modifications associated with the innovative partition concepts occur above all in raw material sourcing, manufacturing, reutilisation logistics, and data-sharing, of which the latter should extend to the end-user. Next to partitioning, the findings can be relevant for other infill components as well, such as: kitchen cabinets, stairs, furniture, and the interior side-sheeting and insulation of walls and ceilings in energy-renovations. Follow-up research and practical efforts should be aimed at the development and testing of products, as well as value propositions regarding ownership: from regular transactions in which ownership shifts to the customer, to more innovative models in which ownership stays with the supplier or shifts to an intermediary actor (e.g. pay-per-use, buy-back or deposit model). Securing healthy circular material flows in the built environment cannot be the objective of one industry, let alone one organisation, but reshuffles whole value networks. This cannot be done without binding agreements and multi‑criteria learning loops. The first emphasises legal frameworks. This is therefore another prime area for future action. The aspect of multi-criteria learning loops, finally, relates to the need for more sophisticated data-exchange, also engaging endusers, which is nowadays rare in housing.